1999
DOI: 10.1063/1.369616
|View full text |Cite
|
Sign up to set email alerts
|

Connection between hydrogen plasma treatment and etching of amorphous phase in the layer-by-layer technique with very high frequency plasma excitation

Abstract: The formation of microcrystalline silicon was investigated employing the layer-by-layer technique with very high frequency plasma excitation. Etching of the deposited layers was found to be a dominant effect during hydrogen plasma treatment. Microcrystalline growth occurred when the thickness of the deposited layer was reduced to a certain value in each cycle. The etching stopped when a noticeable crystalline volume fraction was produced; for long hydrogen treatment times no film growth was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Briefly, the method is based on a short H 2 plasma treatment step during which the gas phase density of SiH 4 ͑i.e., the main etch product released from the film surface͒ is detected. Atomic hydrogen preferentially inserts into strained Si-Si bonds 11,12 resulting in a higher etch rate of a-Si: H relative to c-Si: H. 13,14 The SiH 4 density in the plasma is observed directly by infrared absorption spectroscopy 15 or, alternatively, indirectly by OES. In the latter method, the SiH * emission is detected as originating from SiH 4 etch product dissociation by electron impact, as also reported by Westlake and Heintze.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the method is based on a short H 2 plasma treatment step during which the gas phase density of SiH 4 ͑i.e., the main etch product released from the film surface͒ is detected. Atomic hydrogen preferentially inserts into strained Si-Si bonds 11,12 resulting in a higher etch rate of a-Si: H relative to c-Si: H. 13,14 The SiH 4 density in the plasma is observed directly by infrared absorption spectroscopy 15 or, alternatively, indirectly by OES. In the latter method, the SiH * emission is detected as originating from SiH 4 etch product dissociation by electron impact, as also reported by Westlake and Heintze.…”
mentioning
confidence: 99%
“…Subsequently, after a pump down to Ͻ0.1 Torr, a H 2 plasma treatment of the silicon film was carried out using the same H 2 flow, pressure, plasma power, and substrate temperature as applied under deposition ͑note that these conditions were kept constant within a deposition series͒. The H 2 plasma treatment time was set at Ͻ60 s to diminish H-induced material modification 11,14,18 and the influence of redeposition. 19,20 The time averaged baseline corrected SiH * emission at 414.3 nm proved to scale with the SiH 4 density 13,21 and is used here as a measure for the abundance of etch products during H 2 plasma treatment.…”
mentioning
confidence: 99%
“…In general, the effect of hydrogen dilution on the growth of nc-Si is interpreted in terms of several growth models, including the hydrogen etching model, the surface mobility model, and the chemical annealing model. [6,9,20,21] In our case, the decreased deposition rate and the improved crystalline fraction with increasing hydrogen dilution ratio indicates that hydrogen etching is important in the formation of nc-Si. It is also found that the crystalline fraction of the ultrathin films is apparently lower than that of the thick film under the same hydrogen dilution ratio.…”
Section: Resultsmentioning
confidence: 52%
“…Finally, it is interesting to note that the PF‐PECVD process also bears similarity with reports on the layer‐by‐layer deposition of microcrystalline silicon. In the latter case, the deposition of an ultrathin amorphous silicon film (H 2 /SiH 4 plasma) was alternated by H 2 plasma treatment to crystallize the material 55…”
Section: Resultsmentioning
confidence: 99%